Impact of a multidisciplinary approach in clinical research on cardiovascular prognosis and patients’ quality of life - Pais, Daniela; Amado, Tiago; Monteiro, Pedro; Ferreira, Paulo (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Circulatory system diseases, including cardiovascular diseases, are among the leading causes of death worldwide. This study aimed at implementing a structured project to monitor patients attending clinical research consultations in Cardiology, through a multidisciplinary healthcare team. Research design and methods: A multidisciplinary consultation model was developed and implemented, comparing a control group (Group A, without intervention) and an intervention group (Group B). The study assessed five data collection moments and analysis, including sociodemographic characterization, risk factors, anthropometric assessment, therapeutic adherence (using the Measure Treatment Adherence [MTA] scale), and quality of life (assessed via the EQ Visual Analogue Scale [EQ VAS], part of the EQ-5D-5L scale). Statistical analysis was conducted using SPSS (Statistical Package for the Social Sciences), version 28.0 for Windows. Results and discussion: The anthropometric assessment showed no significant improvement, with both groups maintaining stable weight and BMI values at pre-obesity levels. The parameters remained stable over the follow-up, suggesting that the multidisciplinary intervention and consistent monitoring helped preserve these health indicators. However, significant improvements in therapeutic adherence and quality of life were observed over time in both groups. The increase in therapeutic adherence was significantly greater in Group B, t(432) = -9.046, p < .001, as was the increase in quality of life, t(435) = -5.674, p < .001. Conclusions: The study highlights the value of structured consultations, supported by a trained and professionalized multidisciplinary team, in enhancing health indicators and the quality of life of patients with cardiovascular diseases.